Hábitos alimentarios del Puma concolor (Carnivora: Felidae) en el Parque Nacional Natural Puracé, Colombia - Hernández-Guzmán, Andrés (2011)
Population density in cetaceans can be estimated through photo-identification, mark-recapture, land-based observations and visual estimative. We the aim to contribute with conservation strategies, we used line transects (distance method) to estimate the population density of the river dolphin, S. guianensis, in the estuarine region of Cananéia, Southeastern Brazil. The study, developed from May 2003 until April 2004, dur-ing dry and rainy seasons and different times of the day, included a sampling area divided into three sectors according to their proximity to the open sea: Sector I (the closest to the open sea); Sector II (with a large flow of fresh water and a salient declivity); and Sector III (with a large flow of fresh water and non salient declivity). Onboard random sampling was carried out in all three sectors, and dolphins seen from the bow to 90° on both port and starboard sides, were registered along with their position and distance from the boat. The total density found was 12.41ind/km² (CV=25.53%) with an average of 2.2 individuals per group for both periods of the day, morning and afternoon. Densities also varied between dry and rainy seasons, being lower in the first with 5.77ind/km² (CV=27.87%) than in the second 20.28ind/km² (CV=31.95%), respectively. Regarding the three sectors, a non-causal heterogeneous distribution was found: Sector I was the most populated (D=33.10ind/km², CV=13.34%), followed by Sector II (D=7.8ind/km², CV=21.07%) and Sector III (D=3.04ind/km², CV=34.04%). The aforementioned area, due to its proximity to the open sea, has the highest salinity level and therefore has the greatest chance of holding most of the marine fish schools which can be cornered by dolphins on high declivity areas during fishing activities. This suggests that food availability may be the most important factor on the river dolphin’s distribution in the estuary. Similar studies will contribute to a better understanding of these populations and are essential for future conservation strategies.